Laser beam scanning opto-mechanical systems, devices, and data storage optics - Marshall, Gerald F. (Optical engineering (Marcel Dekker, Inc.), 1985)
Written in an easy-to-read style, this comprehensive guide examines the current knowledge on opto-mechanical laser beam scanning technology.